THE REFORM MECHANISMS POLICY IN GHANA’s PUBLIC FINANCIAL MANAGEMENT - Ahinsah-Wobil, Isaac (Digital Repository of Theses, 2021)
Establishing fiscal stability, establishing laws, realigning revenues, and finding value for expenditure management are all part of public financial management (PFM) techniques that aim to make the government more open and accountable for the benefit of the public. Because of ever-increasing government expenditure, inadequate revenue collection capability, and rising debt levels, Ghana has had a consistent propensity towards budget deficit since independence. Because of the process's high level of intricacy and technical nature, public monitoring and oversight are limited. Furthermore, there is a chance that parliament will fail to protest to a budget influenced by corruption and misallocations that have already been incorporated in the executive's draft budget. As a result, the purpose of this research is to look at the impact of effective financial management reforms on revenue mobilization and expenditure management. The survey design has been used to structure this investigation. Accounting officials and ministry of finance directors were the target audience for financial planning and budgeting activities, while the Internal Audit Agency was the target audience for internal control activities. For revenue mobilization and public financial control, the Ghana Revenue Authority and the Controller and Accountant General's department were also evaluated. Finally, for public finance procurement methods, the Public Procurement Agency was taken into consideration. As a result, the study's sample size will be restricted to the ministries' and agencies' headquarters. Probability and non-probability were both used in this investigation. In order to sample respondents, the study used simple random and purposive sampling procedures. As a result, 180 individuals took part in the research. According to the findings, Ghana's public finance procurement practices are effective in promoting good governance. Furthermore, the study found that procurement policy factors like level of compliance with Public Procurement and Guideline for Disposing of Assets, procurement planning, country executive support, budgetary allocation, and preparation of procurement progress reports have a significant impact on country government performance. Financial planning also assists in determining the country government's financial objectives, policies, procedures, and initiatives. According to the findings, budgeting procedures in Ghana have a favorable impact on good governance. The study also found that public finance decision-making procedures are beneficial to citizens, and as a result, the government will use the findings to develop appropriate rules to control prudent public-fund management. As a result of the study, it was discovered that the government has a solid, transparent revenue and expenditure system that is less expensive to administer and can be deployed to many sections of the country, as well as a reduction in corruption and mismanagement. Despite the fact that revenue mobilization and excellent governance have a statistically significant beneficial association. There is also corporate governance guideline for public companies, with the goal of promoting responsibility, transparency, a performance-based approach, dedication, and integrity. In other words, the report advised that capacity be built to improve oversight functions and internally generated funds, among other things.